Advanced organic nanocomposite coatings for effective corrosion protection - Harb, Samarah Vargas [UNESP] (2020)
Recent advances of nanotechnology allowed a huge step forward in the field of protective coatings based on polymeric composites. The incorporation of nanofillers into organic matrices has proven to enhance essential properties for anticorrosive application, including adhesion to metallic substrates, cross-linked nanostructure that blocks the entrance of corrosive species, mechanical strength to withstand deformation in aggressive environments, and thermal stability for high-temperature applications. Acrylates, epoxy, and polyurethanes coatings modified with inorganic oxides, carbon nanostructures, and clays have provided excellent corrosion protection for metallic surfaces with impedance modulus up to 100 GΩ cm2 and durability of months in corrosive environments. Although less exploited, other polymeric nanocomposites containing fluoropolymers, conducting polymers, polyesters, etc., are promising materials for efficient corrosion protection; therefore, further advances are expected in near future. This chapter gives an overview on the state of the art of nanocomposite high-efficiency protective coatings, giving special emphasis to the potential of organic–inorganic hybrid materials.